Omalizumab as an adjuvant therapy for treating severe atopic dermatitis in children. A series of cases - María García; Alejandro Durán-Crane; Edgardo Chapman; Elizabeth García (Revista Alergia México, 2019)
Background: Atopic dermatitis (AD) is a chronic skin disease that affects 5-20% of children. This disease compromises the quality of life. Omalizumab offers a promising role in the treatment of severe atopic dermatitis.